PENGARUH SALES GROWTH, FIRM AGE, FIRM SIZE DAN LEVERAGE TERHADAP PROFITABILITAS - Putri, Cecillia Heryanti; Iskak, Jamaludin (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study was to examine and obtain empirical evidence of the effect of sales growth, firm age, firm size and leverage on profitability. This study uses multiple regression analysis data processing techniques and then processed using the SPSS version 25 application program. The sample of this study consisted of 25 manufacturing companies in the goods and consumption industry sector which were selected by purposive sampling method that met the criteria of 125 publicly listed companies in Indonesia. Indonesia Stock Exchange in the period 2016 - 2020. The results of research on sales growth have no significant and negative effect on profitability, firm age, firm size and leverage have a significant and positive effect on profitability.